2013
DOI: 10.3109/03091902.2013.794867
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of hypnotic susceptibility on chaotic dynamics of EEG signals during standard tasks of Waterloo-Stanford Group Scale

Abstract: Chaotic features of hypnotic EEG (electroencephalograph), recorded during standard tasks of Waterloo-Stanford Group Scale of hypnotic susceptibility (WSGS), were used to investigate the underlying dynamic of tasks and analyse the effect of hypnotic depth and concentration on EEG signals. Results demonstrate: (1) More efficiency of Higuchi dimension in comparison with Correlation dimension to distinguish subjects from different hypnotizable groups, (2) Channels with significantly different chaotic features amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Several studies described EEG correlates of hypnosis, but their results were often inconsistent owing to methodological differences [ 9 , 17 , 18 , 19 , 46 ]. The aim of the present study was to detect the role of formal hypnotic induction in the EEG activity of highs that are aware of their hypnotic score and waiting for hypnotic induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies described EEG correlates of hypnosis, but their results were often inconsistent owing to methodological differences [ 9 , 17 , 18 , 19 , 46 ]. The aim of the present study was to detect the role of formal hypnotic induction in the EEG activity of highs that are aware of their hypnotic score and waiting for hypnotic induction.…”
Section: Discussionmentioning
confidence: 99%
“…Within each three-minute-long window (i.e., R OE , R CE , IND1, IND2, NH, POST), we estimated the PSD with the Welch method using five-second-long windows with an overlap of 80%. The PSD was then integrated in the canonical EEG frequency bands, i.e., delta (1-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Signal Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the view of identifying more specific markers of hypnotic susceptibility, additional studies applied nonlinear measures to EEG of subjects under hypnosis [21][22][23][24][25][26]. In particular, it was observed that complexity was higher among HS compared to MS and LS using both Recurrence Quantification Analysis (RQA) and Fractal Dimension Analysis (FDA) [21,25]. Furthermore, the combination of RQA with Detrended Fluctuation Analysis (DFA) allowed to distinguish HS from LS and to predict subjects' level of hypnotizability [22].…”
Section: Introductionmentioning
confidence: 99%